Exploring Pre-Service Chemistry Teachers' Pedagogical Scientific Language Knowledge - Corinna Mönch; Silvija Markic (MDPI AG, 2022)
Chemish, as the scientific language of chemistry, is essential for communicating in and understanding chemistry. At the same time, Chemish is one of the major difficulties in teaching and learning chemistry in the school context. Although in recent years the importance of language in general and scientific language in particular has been pointed out and much research has been carried out on these topics, less is known about (pre-service) chemistry teachers' knowledge of teaching and learning the scientific language in chemistry classes. Thus, the research on Pedagogical Scientific Language Knowledge (PSLK) is missing. As this knowledge is crucial for (future) chemistry teachers to teach chemistry, in our survey, we seek to evaluate the extent of 41 pre-service chemistry teachers' PSLK. The answers are analyzed using qualitative content analysis. Results show that pre-service chemistry teachers' content knowledge resembles the level of knowledge for higher secondary schools. Likewise, the pre-service chemistry teachers have a lack of incisive pedagogical content knowledge: although recognizing problems within Chemish, the pre-service chemistry teachers hardly address those and do not focus on the characteristics of Chemish while explaining scientific terms. On this basis, implications for further university chemistry teacher education and research will be drawn.